STYLE-SPECIFIC INDIVIDUALITY (American Journal of Interdisciplinary Research and Development, 2022)
The article discusses the individuality of the style, the innovation of the artist depends on the internal factors that affect him, and analyzes the work of Alisher Navoi “Mahbub ul-kulub” are studied.